Food literacy competencies in youth – a mini-review - Groufh-Jacobsen, Synne; Medin, Anine Christine (Frontiers in Public Health, 2023)
Introduction: Young people`s transition into adulthood is an opportunity in the life course to establish adequate eating behaviors, hence exploring food literacy competencies in this period of life is especially important. Food literacy has recently gained increased attention in adults, adolescents, and younger children, but less is published about youth. This paper aims to summarize what tools have been used to measure food literacy and the sub-competence nutrition literacy in youth aged 16-24 years in the previous five years. Methods: A mini-literature review was conducted in MEDLINE and EMBASE via Ovid, in September 2022. Study eligible criteria had to be an original article, using a tool to quantitatively assess food literacy and/or nutrition literacy, including participants between 16-24 years, full text available in English, published between 2017-2022. Results: A total of 958 articles were identified, of which 385 duplicates were removed. Thus, 573 articles were screened by title/abstract. Finally, nine articles were eligible for data extraction of which four proposed a tool to measure food literacy and five proposed a tool to measure nutrition literacy. Discussion and conclusion: Although four studies claimed to measure food literacy, none of these used tools comprehensive enough to measure all aspects of food literacy, and only one was validated in young people. This study shows that only few tools exist for the measurement of food literacy in youth, and those available are scant. Further work is needed to develop a food literacy tool for youth.